On the dynamics of the human endocrine pancreas and potential consequences for the development of type 1 diabetes - Skog, Oskar (Acta Diabetol, 2019)
Little is known about the human islet life span, and beta-cell neogenesis is generally considered rare in adults. However, based on available data on beta-cell proliferation, calculations can be made suggesting that the dynamics of the endocrine pancreas is considerable even during adulthood, with islet neogenesis and a sustained increase in size of already formed islets. Islet-associated hemorrhages, frequently observed in most mammals including humans, could account for a considerable loss of islet parenchyma balancing the constant beta-cell proliferation. Notably, in subjects with type 1 diabetes, periductal accumulation of leukocytes and fibrosis is frequently observed, findings that are likely to negatively affect islet neogenesis from endocrine progenitor cells present in the periductal area. Impaired neogenesis would disrupt the balance, result in loss of islet mass, and eventually lead to beta-cell deficiency and compromised glucose metabolism, with increased islet workload and blood perfusion of remaining islets. These changes would impose initiation of a vicious circle further increasing the frequency of vascular events and hemorrhages within remaining islets until the patient eventually loses all beta-cells and becomes c-peptide negative.